Pendidik dalam Perspektif Al-Quran dan Pendidikan Islam - Juarman Juarman; Arivaie Rahman; Sri Erdawati (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
This article discussed educators from the perspective of the Al-Quran and Islamic education. Educators are an important element in the Islamic education system. Educators are determinants of the intellectual and moral success of students. So it is interesting to ask how educators in the perspective of the Al-Quran and Islamic education. To answer these research questions, this study used library research and descriptive-analysis methods. The results of this study revealed that the subject of educators according to the Al-Quran is very diverse and forms a hierarchy, Allah, Rasulullah, parents, and teachers. Whereas the predicate that is usually carried by an educator in the Islamic education tradition is Ustadz, Mu'allim, Mursyid, Murabbi, Mudarris, and Mu'addib. Each of these names has almost the same meaning but has its own definitions and characteristics.